KAJIAN PEROVSKITE LA0,73CA0,27MN1-XCUXO3 DENGAN 0 - Gunanto, Y. E.; Sinaga, K.; Purwanto, A.; Kurniawan, B.; Poertadji, S.; Steven, E.; Brooks, J. S. (Jurnal Spektra, 2014)
We have performed the synthesis and characterization of materials La0.73Ca0.27Mn1-xCuxO3 for 0 <x< 0.19 using neutron scattering diffraction (HRPD) and SQUID.All the samples are already in phase with the crystal structure orthorombic and space group P nma. Parameters of the Mn-O bond length obtained from the charactyerization HRPD. From the parameters of Mn-O bond length can be determined the value of Jahn-Teller distortion. The greater x will result in an average radius of position B (<rB>) increasing and the tolerance factor t decreasing. From the characterization of the SQUID was found that the maximum value of conductivity for Cu-doped samples will be lower when compare to the sample without doping, except for Cu=0.10. If the value of the conductivity is getting smaller, the activation energy will be higher. Keywords: Jahn-Teller distortion, factor tolerance, conductivity, activation energy